High-density bimodal bentonite blends for hydraulic sealings at the Ibbenbüren coalmine. (2nd January 2018) - Wolters, Felicitas; Baille, Wiebke; Emmerich, Katja; Schmidt, Eva; Wolters, Christian; Königer, Franz; Kunz, Jürgen; Krase, Volker; Schellhorn, Matthias
Abstract: The two high-pressure water-retaining dams at the Ibbenbüren coalmine in Münsterland (Germany) have to perform reliably under the induced tension caused by further exploitation of the current mining area. The load-bearing and the sealing functions of the new barriers were separated and new sealing materials were developed. An innovative multilayer sealing system of bentonite and sandwiched equipotential layers (SANDWICH) supporting homogeneous swelling and sealing, independent of formation water (Nüesch et al., 2002), was applied in this project. A testing program of strain-controlled swelling pressure tests on compacted bentonite specimens and on a bentonite/sand mixture was conducted to ensure an adequate potential for swelling-pressure development. The measurements under constant volume for dry densities between 1.45 g/cm 3 and 1.67 g/cm 3 showed an evolving swelling pressure between 1.04 and 1.8 MPa for 100% bentonite samples. Straincontrolled oedometer tests for zero strain and step-wise applied strain up to 2% revealed that a sufficient magnitude of swelling pressure existed at maximum applied strain.